Pollen percentage thresholds of Abies alba based on 13-year annual records of pollen deposition in modified Tauber traps: perspectives of application to fossil situations - Pidek, I. A.; Svitavská-Svobodová, H. (Helena); van der Knaap, W. O.; Magyari, E. (Review of Palaeobotany and Palynology, 2013)
The study aims: to estimate pollen thresholds for fir presence/absence in Bohemia (Czech Republic, Šumava and Krkonoše mountains) and Poland (Roztocze) on the basis of modified Tauber pollen traps; to use these thresholds for tracing fir presence in pollen diagrams from Poland (Slone and Bezedna lakes and Polesie; and to investigate how the percentage presence/absence threshold can be used to trace the occurrence and abundance of fir trees in the Sumava Mts based on the pollen diagrams of Rokytecka slat' and Mrtvy luh. Percentage thresholds range from 0.3% in Krkonose where fir trees are not present in tundra within 4 km to 22% in fir-dominated woodland of the Roztocze. Evidence of strong underrepresentation of fir in the pollen deposition was confiremed. Fir expansion during the Holocene in Poland and in Bohemia is reconsidered in the last conclusions.